Intertemporal Price Discrimination and Consumer Demand - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 1997)
Under a particular class of utility functions, intertemporal price discrimination (IPD) is not feasible. That is, customers cannot be made to pay different prices for a durable good at different points in time. Other factors such as falling costs, and differing discount rates between buyers and sellers have been found to make intertemporal pricing schemes feasible, or even profitable. None of these factors, however, were fundamental demand differences which give rise to static price discriminations. In this paper we argue that IPD is indeed feasible and sometimes profitable, if only we allow for a nondurable good in the utility function. A simple additively separable utility is examined first, which is then extended to a nonseparable utility function which allows richer substitution/complementary relations between the durable and the nondurable goods. This may help us to better understand the similarities between static and intertemporal price discriminations.